Bridging the gap: reflections on co-creation in knowledge translation - Marjolijn Ketelaar; Maureen Bult; Marike Willems-op Het Veld; Karen van Meeteren; Marij Roebroeck; Jeanine Voorman (Research Involvement and Engagement)
Abstract Background To address the research-practice gap, knowledge translation is a crucial step in which co-creation, including patient and public involvement (PPI), is key. We performed a knowledge translation project in co-creation with all stakeholders as equal partners in the design and decision-making process. The project was based on scientific knowledge of a large research program on development of children and young adults with cerebral palsy (CP). It aimed to synthesize the knowledge on development of children and youth with CP, and to develop tools that are useful for health care professionals, persons with CP, and families. This paper describes the knowledge translation process applied in the project, specifically how the ‘key principles’ employed to ensure co-creation were operationalised, including reflections on the process and lessons learned. Main body Three key principles were defined to guarantee involvement of all stakeholders as equal partners in the design and decision-making process: a shared vision on collaboration and partnership, transparency: open and honest communication, and co-creation as a stepwise, iterative process. These key principles are based on literature and earlier experiences. They are described in more detail and are illustrated with examples from the knowledge translation project. The iterative co-creation process can be regarded as a cyclical process, including planning, conducting, reflection, evaluation, and refining the product and the process. This means that there was a continuous learning cycle in which we learned from the challenges and successes, now and then taking a step back. Based on our reflections the most important lessons learned are summarized. Conclusion The key principles were helpful in this knowledge translation process. Reflecting on these principles during the joint journey secured co-creation with all stakeholders as equal partners in the design and decision-making process. By sharing experiences, key principles, examples and lessons learned we intend to advance knowledge in PPI, and to inspire others.